Divining the Etruscan world: the brontoscopic calendar and religious practice - Turfa, Jean MacIntosh (Cambridge University Press, 2012)
The Etruscan Brontoscopic Calendar is a rare document of omens foretold by thunder. It long lay hidden, embedded in a Greek translation within a Byzantine treatise from the age of Justinian. The first complete English translation of the Brontoscopic Calendar, this book provides an understanding of Etruscan Iron Age society as revealed through the ancient text, especially the Etruscans' concerns regarding the environment, food, health and disease. Jean MacIntosh Turfa also analyzes the ancient Near Eastern sources of the Calendar and the subjects of its predictions, thereby creating a picture of the complexity of Etruscan society reaching back before the advent of writing and the recording of the calendar.